BENEFITS OF BREAST RECONSTRUCTION ON THE QUALITY OF LIFE OF WOMEN WITH BREAST CANCER - Assunção, Silvaleide Ataides; Rahal, Rosemar Macedo Sousa (Mastology, 2021)
Objectives: Mastectomy is the most effective form of treatment in cases of breast cancer, promoting biopsychosocial consequences to patients. Thus, the objective is to integrate and analyze data from studies carried out, highlighting the positive impact of breast reconstruction based on the available medical literature, contributing to a better understanding of the importance of such a procedure to improve the quality of the services provided. Methodology: This is a descriptive research based on a review of the medical literature available through a survey of publications from the past 12 years in the PubMed, Lilacs, and MedLine databases. The following descriptors were used: “reconstruction” AND “mammary” AND “benefits”. Results: It was noted that women who underwent breast reconstruction had a high level of satisfaction with the quality of life in the psychological and social relations domains. Most of them have a medium to a very high degree of satisfaction, suggesting that the postoperative functional adaptation was not negatively affected by the additional anatomical changes imposed by breast reconstruction. There are also benefits in the sexual life of these patients, who find a degree of satisfaction between good and excellent. In the literature, there are reports of better social interaction, job satisfaction, higher levels of satisfaction, and lower incidence of depression among women who underwent immediate reconstruction after 1 year of surgery. However, such benefits do not seem to be universally found when women undergoing immediate reconstruction are compared with those treated conservatively, with quadrantectomies or lumpectomies. Conclusion: Breast reconstruction, in addition to being a right under Law 12.802, is a procedure that reduces the sensation of mutilation and alleviates the absence of the breast. Therefore, when indicated procedures, such as prostheses, tissue expansion or flaps, after mastectomy, reinforce the woman’s self-esteem because the breast is understood in society as a fundamental characteristic for femininity.